Change in Health Literacy Over 2 Years in Older Adults With Diabetes. (September 2013) - Morris, Nancy S.; MacLean, Charles D.; Littenberg, Benjamin
Purpose: The purpose of this study was to evaluate the stability of health literacy in adults with diabetes over time. Understanding the dynamic nature of health literacy is important when tailoring health messages, especially those targeted at the management of chronic health conditions. Method: This was a descriptive longitudinal study of 751 adults with diabetes randomly selected from primary care practices in the Vermont Diabetes Information System study between July 2003 and December 2007. Participants were interviewed and completed questionnaires upon entrance into the study and again 24 months later. Health literacy was measured with the Short Test for Functional Health Literacy of Adults. Participants also completed the SF-12 and the Self-Administered Comorbidity Questionnaire and self-reported their sex, income, education, marital status, race/ethnicity, health insurance, duration of diabetes, and problems with vision. Results: A significant decrease in health literacy was noted over 24 months. The largest decrease was in adults ≥65 years of age and those with higher physical function at baseline. Smaller declines were noted for women and participants who were white, higher educated, poly-pharmacy users, and with fair to excellent vision. Conclusions: Health literacy exhibits decline with increasing age among adults with diabetes. Individual variability in health literacy has implications for the best timing and approach to provide self-management education and support.